2004
DOI: 10.2337/diabetes.53.2.454
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Inducible Nitric Oxide Synthase Reduces Myocardial Damage During Ischemia Reperfusion in Streptozotocin-Induced Hyperglycemic Mice

Abstract: We investigated the role of inducible nitric oxide synthase (iNOS) on ischemic myocardial damage and angiogenic process in genetically deficient iNOS (iNOS ؊/؊ ) mice and wild-type littermates (iNOS ؉/؉ ), with and without streptozotocin-induced (70 mg/kg intravenously) diabetes. After ischemia (25 min) and reperfusion (120 min), both iNOS ؉/؉ and iNOS ؊/؊ diabetic mice (blood glucose 22 mmol/l) had myocardial infarct size greater than their respective nondiabetic littermates (P < 0.01). Myocardial infarct siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 38 publications
3
73
0
2
Order By: Relevance
“…Our results are consistent with previous studies of acute ischemia and reperfusion in which administration of semi-selective inhibitors of iNOS or iNOS-null mice enhanced cardiac performance and/or reduced myocardial infarct size (34 -37). Previous studies showed that iNOS played critical roles in diabetes and I/R in the heart, because iNOS-null mice displayed protection from the adverse effect of this injury, especially in diabetes (38). Our findings definitively link RAGE and RAGE signaling in endothelial cells and mononuclear phagocyte to generation of NO and pathogenic oxidant stress species in the diabetic heart.…”
Section: Rage and Nossupporting
confidence: 62%
“…Our results are consistent with previous studies of acute ischemia and reperfusion in which administration of semi-selective inhibitors of iNOS or iNOS-null mice enhanced cardiac performance and/or reduced myocardial infarct size (34 -37). Previous studies showed that iNOS played critical roles in diabetes and I/R in the heart, because iNOS-null mice displayed protection from the adverse effect of this injury, especially in diabetes (38). Our findings definitively link RAGE and RAGE signaling in endothelial cells and mononuclear phagocyte to generation of NO and pathogenic oxidant stress species in the diabetic heart.…”
Section: Rage and Nossupporting
confidence: 62%
“…48) The difference in the type of diabetes may be the reason for these differences. [49][50][51] Therefore, the effect of IP may be decreased in type 2 diabetes mellitus with hyperinsulinemia, although it has not yet been clarified in type 1 diabetes mellitus without hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nitric oxide, protein kinase C and K ATPchannels are involved in IPC in non-diabetic subjects and that nitric oxide metabolism is impaired in diabetic subjects. However, in Type 1 diabetic animals the presence of a functional inducible nitric oxide synthase gene (producing high levels of nitric oxide) seems to aggravate ischaemic damage [21]. Hyperglycaemia is considered a major determinant of the extent of myocardial infarction in experimentally induced Type 1 diabetes and even in the absence of diabetes [22,23].…”
Section: Discussionmentioning
confidence: 99%